Preference for novel biomedical HIV pre-exposure prophylaxis methods among adolescent girls and young women in Kampala, Uganda: a mixed methods study - Mayanja, Yunia; Kayesu, Ivy; Kamacooko, Onesmus; Lunkuse, Jane Frances; Muturi-Kioi, Vincent; Price, Matt; Kosidou, Kyriaki; Ekström, Anna Mia (Frontiers in Public Health, 2024)
Novel HIV pre-exposure prophylaxis (PrEP) methods including a potential future HIV vaccine, will increase prevention options for adolescent girls and young women (AGYW) at high risk of HIV infection in Eastern and Southern Africa, yet data on AGYW´s preferences for various PrEP methods is limited. We investigated preferences for five biomedical PrEP methods (oral, injectable, vaginal ring, implant, HIV vaccine) among 14-24-years-old AGYW in Kampala, Uganda Methods From January to December 2019, we conducted a mixed methods study including 265 high-risk AGYW. After receiving two education sessions on the five PrEP methods, participants were asked about their "most preferred PrEP method". Multinomial logistic regression (oral PrEP as reference category) was used to determine participant characteristics associated with method preference. Results are presented as adjusted relative risk ratios (aRRR) with 95% confidence intervals (CI). In-depth interviews were conducted with 20 selected participants to examine reasons influencing PrEP preferences and suggestions for method improvements. Transcripts were analyzed thematically.Participants preferred methods were: HIV vaccine (34.7%), oral PrEP (25.7%), injectable PrEP (24.9%), PrEP implant (13.6%), and vaginal ring (1.1%). Preference for injectable PrEP increased with every year of age (aRRR 1.22; 95% CI 1.04-1.44) and among participants with chlamydia or gonorrhoea (aRRR 2.53; 95% CI 1.08-5.90), while it was lower among participants having sexual partner(s) living with HIV or of unknown HIV status (aRRR 0.30; 95% CI 0.10-0.91). Preference for PrEP implants also increased with age (aRRR 1.42; 95% CI 1.14-1.77) and was strong among participants having ≥10 sexual partners in the past 3 months (aRRR 3.14; 95% CI 1.16-8.55), while it was lower among those with sexual partner(s) living with HIV or of unknown HIV status (aRRR 0.25; 95% CI 0.07-0.92). PrEP method preference was influenced by product attributes and prior experiences with similar product forms commonly used in health care.AGYW have varied preferences for biomedical PrEP method and those with higher sexual behavioral risk prefer long-acting methods. As we anticipate more available PrEP options, oral PrEP use should be supported among AGYW, especially for those with sexual partners living with HIV or of unknown HIV status.